Pengaruh Pendapatan, Budaya dan Religiusitas Terhadap Kepatuhan Muzakki dalam Membayar Zakat Profesi di Sidoarjo - Rani; Faujiah, Ani (STEI Kanjeng Sepuh Gresik Jawa Timur, 2024)
This study examines the influence of income, culture, and religiosity on muzakki's compliance in paying professional zakat in Sidoarjo, East Java. The phenomenon of low compliance in paying professional zakat, despite its great potential, encourages this research. Professional zakat is an important part of Islamic teachings that plays a role in alleviating poverty and improving the welfare of the people, but there are still many muzakki who do not comply. This study uses a quantitative method with a survey approach, collecting data from 150 respondents by purposive sampling. Data analysis was carried out using multiple linear regression. The results showed that income and culture had a positive and significant influence on muzakki compliance, with a t-value of 0.229 (> 0.05) for income and 0.351 (> 0.05) for culture, respectively. However, religiosity had no significant effect with a t-value of 0.002 < 0.05. This research is expected to increase professional zakat payment compliance and become a reference for zakat institutions and local governments in formulating effective strategies and policies.